Informality and firm performance in Myanmar - Hanna Berkel; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Using a novel panel survey of enterprises in Myanmar, we compare the performance of manufacturing firms by three different informality definitions. The first is binary, based on whether firms pay taxes. The second captures five categories of registration with the authorities, and the third definition relates to three groupings of the informality status of a firm's workers. Depending on the informality concept used, formalization has positive, insignificant, and negative performance outcomes. However, our analysis shows that independent of the informality definition, differences between formalizers and non-formalizers are mostly because of disparities in the number of employees, capital, and use of power-driven machinery. Education, business practices, gender, location, and sector only play a role for some of the definitions and performance variables.
Keywords: D22; O17; N65; 330; firms; informality; Myanmar; business registration; manufacturing